2021
DOI: 10.1016/j.isci.2021.102281
|View full text |Cite
|
Sign up to set email alerts
|

Bracovirus-mediated innexin hemichannel closure in cell disassembly

Abstract: Summary Cell-cell communication is necessary for cellular immune response. Hemichannel closure disrupts communication between intracellular and extracellular environments during polydnavirus-induced immunosuppression in invertebrates. However, the effects of hemichannel closure on cellular immune response are unclear. Here, we examined apoptotic body formation triggered by hemichannel closure in hemocytes of Spodoptera litura infected with bracovirus from the parasitic wasp, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…We have previously shown that MbBV induces AB formation by shutting down hemocyte hemichannels to activate caspase-3 and cleave Innexins (Inxs), triggering apoptotic cell disassembly ( 4 ). However, the biological role of MbBV-induced ABs in immunosuppression remains poorly understood ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that MbBV induces AB formation by shutting down hemocyte hemichannels to activate caspase-3 and cleave Innexins (Inxs), triggering apoptotic cell disassembly ( 4 ). However, the biological role of MbBV-induced ABs in immunosuppression remains poorly understood ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the biological role of MbBV-induced ABs in immunosuppression remains poorly understood ( Figure 1A ). To determine whether MbBV suppresses the immune response via AB phagocytosis, we used ABs-induced by reBac-Inx3 ( 4 , 31 , 32 ) as a positive control, detectable using 6 × His tag ( Figure S1A ) to allow us to determine whether ABs can be phagocytosed by Sf9 cells. The ABs induced by reBac-Inx3 were divided equally ( Figure S1B ) for direct protein quantification from the ABs, while the other was incubated with Sf9 cells ( Figures 1B–D ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations